2015
DOI: 10.1016/j.socec.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The need to belong and the value of belongings: Does ostracism change the subjective value of personal possessions?

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription. The first author"s contribution was supported by a grant from the Leverhulme Trust (RP2012-V-022) and a PhD studentship from the University of Essex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 51 publications
1
32
1
Order By: Relevance
“…The possibility that our manipulation did not work is further weakened by the fact that, in past research, Cyberball was effective in affecting self-reported perceptions of social exclusion (Van Beest, Williams, & Van Dijk, 2011;Walasek et al, 2015;Williams & Jarvis, 2006;Zadro et al, 2004) and had an impact on relevant brain activity (Eisenberger, Lieberman, & Williams, 2003;Preller et al, 2016) and behaviours (Lustenberger & Jagacinski, 2010;Warburton, Williams, & Cairns, 2006). In our studies, despite the significant and robust effect of a lowered need for belonging, we observed no differences in performance in the judgement and decision-making tasks.…”
Section: All Alone But Not Bad Decision-makerscontrasting
confidence: 66%
See 2 more Smart Citations
“…The possibility that our manipulation did not work is further weakened by the fact that, in past research, Cyberball was effective in affecting self-reported perceptions of social exclusion (Van Beest, Williams, & Van Dijk, 2011;Walasek et al, 2015;Williams & Jarvis, 2006;Zadro et al, 2004) and had an impact on relevant brain activity (Eisenberger, Lieberman, & Williams, 2003;Preller et al, 2016) and behaviours (Lustenberger & Jagacinski, 2010;Warburton, Williams, & Cairns, 2006). In our studies, despite the significant and robust effect of a lowered need for belonging, we observed no differences in performance in the judgement and decision-making tasks.…”
Section: All Alone But Not Bad Decision-makerscontrasting
confidence: 66%
“…Then, participants completed a self-esteem boosting exercise where they listed their best qualities (Walasek, Matthews, & Rakow, 2015) followed by an assessment of their current mood and self-esteem level. Participants were then debriefed and informed that their co-players were computer-based.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing amount of empirical and theoretical work has attempted to describe the processes through which an individual develops a special bond with his/her possessions (Beggan, 1992;Pierce, Kostova, & Dirks, 2003;Walasek, Matthews, & Rakow, 2015). One key theoretical framework that describes this process is self-extension theory (Belk, 1988;Dittmar, 1992;Pierce et al, 2001;2003), according to which possessions become part of our extended self, ultimately becoming incorporated into our own self-definition.…”
Section: Psychological and Factual Status Of Ownershipmentioning
confidence: 99%
“…Note that all experiments ended with a debriefing, after which everyone completed a self-esteem boost where they listed their best qualities followed by an assessment of their current mood and self-esteem. This was shown to effectively remedy the negative effect of social exclusion (Juanchich et al, 2018;Walasek, Matthews, & Rakow, 2015). Finally, all participants reported whether they experienced any issues with the Cyberball game and if they had played Cyberball before.…”
Section: Post Exclusion Survey and Checking Measuresmentioning
confidence: 99%